Effects of an emotional intelligence program in variables related to the prevention of violence - Garaigordobil, Maite; Peña-Sarrionandia, Ainize (Frontiers in Psychology, 2015)
In recent decades, numerous studies have shown a significant increase in violence during childhood and adolescence. These data suggest the importance of implementing programs to prevent and reduce violent behavior. The study aimed to design a program of emotional intelligence for adolescents and to assess its effects on variables related to violence prevention. The possible differential effect of the program on both genders was also examined. The sample comprised 148 adolescents aged from 13 to 16 years. The study used an experimental design with repeated pretest-posttest measures and control groups. To measure the variables, 4 assessment instruments were administered before and after the program, as well as in the follow-up phase (one year after the conclusion of the intervention). The program consisted of 20 one-hour sessions. The pretest-posttest ANCOVAs showed that the program significantly increased: (1) emotional intelligence (attention, clarity, emotional repair); (2) assertive cognitive social interaction strategies; (3) internal control of anger; and (4) the cognitive ability to analyze negative feelings. In the follow-up phase, the positive effects of the intervention were generally maintained and, moreover, the use of aggressive strategies as an interpersonal conflict-resolution technique was significantly reduced. Regarding the effect of the program on both genders, the change was very similar, but the boys increased assertive social interaction strategies, attention, and emotional clarity significantly more than the girls. The importance of implementing programs to promote socio-emotional development and prevent violence is discussed.